Power QualityAnalysis by Calculating Total Harmonic Distortion at Different Sag Values Using Dynamic Voltage Restorer - Satyam Patel; MPS Chawla; Sandeep Bhongade (Journal of Power Electronics and Devices, 2018)
Power Quality is the most important issue in distribution network due to frequency variation, voltage dip, voltage swell and Harmonic Distortion. The Paper deals with the compensation of voltage dip using a series connected device Known as Dynamic voltage Restorer, which is relatively less expensive, small in size, higher energy storage and power efficient device as compared to other custom power devices. In this paper, two level Pulse Width Modulation system is utilized to adjust the voltage plunge at various sag esteems. The Total Harmonic Distortion esteems are likewise determined utilizing Fast Fourier Transform investigation and compared with and without filter section utilized in the DVR unit and the rate enhancement in the Total harmonic Distortion by utilizing channel unit is likewise assessed.